Early and mid-term outcome of patients with low-flow–low-gradient aortic stenosis treated with newer-generation transcatheter aortic valves - Fraccaro, Chiara; Tarantini, Giuseppe; Rosato, Stefano; Baglio, Giovanni; Biancari, Fausto; Barbanti, Marco; Tamburino, Corrado; Bedogni, Francesco; Ranucci, Marco; Ussia, Gian Paolo; Seccareccia, Fulvia; D'Errigo, Paola (Frontiers in Cardiovascular Medicine, 2022)
Patients with non-paradoxical low-flow–low-gradient (LFLG) aortic stenosis (AS) are at increased surgical risk, and thus, they may particularly benefit from transcatheter aortic valve replacement (TAVR). However, data on this issue are still limited and based on the results with older-generation transcatheter heart valves (THVs). The aim of this study was to investigate early and mid-term outcome of TAVR with newer-generation THVs in the setting of LFLG AS. Data for the present analysis were gathered from the OBSERVANT II dataset, a national Italian observational, prospective, multicenter cohort study that enrolled 2,989 consecutive AS patients who underwent TAVR at 30 Italian centers between December 2016 and September 2018, using newer-generation THVs. Overall, 420 patients with LVEF ≤50% and mean aortic gradient <40 mmHg were included in this analysis. The primary outcomes were 1-year all-cause mortality and a combined endpoint including all-cause mortality and hospital readmission due to congestive heart failure (CHF) at 1 year. A risk-adjusted analysis was performed to compare the outcome of LFLG AS patients treated with TAVR (n = 389) with those who underwent surgical aortic valve replacement (SAVR, n = 401) from the OBSERVANT I study. Patients with LFLG AS undergoing TAVR were old (mean age, 80.8 ± 6.7 years) and with increased operative risk (mean EuroSCORE II, 11.5 ± 10.2%). VARC-3 device success was 83.3% with 7.6% of moderate/severe paravalvular leak. Thirty-day mortality was 3.1%. One-year all-cause mortality was 17.4%, and the composite endpoint was 34.8%. Chronic obstructive pulmonary disease (HR 1.78) and EuroSCORE II (HR 1.02) were independent predictors of 1-year mortality, while diabetes (HR 1.53) and class NYHA IV (HR 2.38) were independent predictors of 1-year mortality or CHF. Compared with LFLG AS treated with SAVR, TAVR patients had a higher rate of major vascular complications and permanent pacemaker, while SAVR patients underwent more frequently to blood transfusion, cardiogenic shock, AKI, and MI. However, 30-day and 1-year outcomes were similar between groups. Patients with non-paradoxical LFLG AS treated by TAVR were older and with higher surgical risk compared with SAVR patients. Notwithstanding, TAVR was safe and effective with a similar outcome to SAVR at both early and mid-term.